Pengembangan Media Game Edukasi untuk Meningkatkan Pemahaman Siswa pada Mata Pelajaran IPA Kelas IV - Mufidah, Eli; Lestari, Putri Dwi (IBTIDA', 2022)
This study aims to develop learning media for android-based educational games in science subjects for energy sources, so as to increase the activity of students and increase their understanding of various energy sources and their uses. This type of research is research and development (R&D), which refers to the ADDIE development model (Analysis, Design, Development, Implement, and Evaluation). The data obtained will be analyzed with descriptive quantitative and qualitative data. The feasibility of learning media for Android-based educational games from the research results is "very feasible" to be used as a learning medium for fourth grade students. This can be seen from the results of the percentage of media expert validation of 82%, material expert validation of 88%, and linguistic expert validation of 88%. The three criteria are declared to have valid categories with additional input and general suggestions that are used as consideration in improving educational game media. Furthermore, based on the questionnaire responses, students obtained results of 92.9% which indicated the "very good" criteria. Meanwhile, based on the results of the class tests (pre-test and post-test) the average value was initially only 55.6, which increased to 85.6 after using educational game media.